Progressing policy toward a risk/need informed sanctioning model - D'Amato, Christopher (Criminology & public policy, 2021)
Research This study examined whether risk/need assessment results coincided with the placement of defendants into six types of sanctions among convicted adults from 11 counties in one state. Crosstabulations highlighted that individuals’ risk/need levels corresponded to the placement of low-risk/need individuals to probation and high-risk/need individuals to prison; however, intermediate sanctions were rarely used for any risk/need level and some low- and moderate-risk/need individuals were sentenced to prison when convicted of offenses that do not typically result in incarceration. Policy Implications The results suggest that courts should adopt an evidence-informed sanctioning model by using risk/need assessments to inform sentencing decisions. Further, states should utilize intermediate sanctions more often to divert individuals convicted of less serious offenses from prison. Finally, judges should avoid sentencing low-risk/need individuals to prison whenever possible. These changes could help courts to better match individuals’ risk/need level to sanctions.